ECMO management for severe pulmonary embolism with concurrent cerebral hemorrhage: a case report - Xie, Lutao; Lan, Pin; Liu, Mingjun; Zhou, Kechun (Frontiers in Cardiovascular Medicine, 2024)
Background: Acute pulmonary embolism (APE) is a common and potentially fatal cardiovascular disease that can lead to sudden cardiac arrest in severe cases. When conventional cardiopulmonary resuscitation measures fail to achieve the return of spontaneous circulation (ROSC) in patients with APE, venoarterial extracorporeal membrane oxygenation (ECMO) becomes a viable therapeutic option. As an advanced life support treatment, ECMO ensures the perfusion of critical organs, providing sufficient time for interventions necessary for ROSC. Case introduction: We report the case of a patient who experienced cardiac arrest due to pulmonary embolism. During the treatment, the patient received two sessions of external cardiopulmonary resuscitation (ECPR) as supportive care and experienced cerebral hemorrhage. Ultimately, the patient improved and was discharged following support from extracorporeal membrane oxygenation (ECMO), careful anticoagulation strategies, and intervention with balloon pulmonary angioplasty.ECMO can serve as an important life support technology for patients with severe APE. Through a cautious anticoagulation therapy, not only was the ECMO support successfully maintained but also was further deterioration of cerebral hemorrhage effectively prevented. For patients with concurrent main pulmonary artery embolism and bleeding, balloon pulmonary angioplasty may be an option.